Determination of CD4+ T- Lymphocytes in Healthy Children of Kathmandu - Karn, Sapana; Bhattarai, Manjula; Rauniyar, Ramanuj; Adhikari, Anurag; Karna, Pratik; Upadhyay, Bishnu Prasad; gupta, Birendra prasad (Journal of Nepal Health Research Council, 2018)
Background: The cluster differentiation (CD) of T-cell is the good marker for the immunological competence study. Nepal does not have a reference value for CD4+ T cell count and percentage for children, which severely limits the prospect of pediatric prognosis.Methods: This cross-sectional study was conducted in Kathmandu valley where total 207 children of age 0-14 year age group were recruited in this study. We analyzed 50 cord blood and 157 peripheral blood samples in order to calculate the absolute count of CD4+ T lymphocyte using Fluorescence-activated cell sorting methodology.Results: The reference range for absolute CD4+ T cell count was found to be 634-4040 cells/µL(mean1470; median: 1335 and 95% CI [1322-1617]) for male children and 491-2922 cells/µL (mean: 1443 median: 1326 and95% CI [1298-1588]) for the female children.We also observed elevated CD4 to the CD3 ratio in younger children (0.67 from cord blood Vs 0.53 from 10-14yr) compared to older ones.Conclusions: The observed CD4+ T cell counts among healthy children of Kathmandu highlights the gender differences skewed for male as well the need of defining specific reference values for other lymphocyte subsets as well in a country like Nepal which has a population with diverse genetic and socio-cultural parameters.Keywords: CD4+ T lymphocyte; children; HIV; immunophenotyping; Kathmandu; Nepal.